1997
DOI: 10.1002/(sici)1098-237x(199701)81:1<91::aid-sce5>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Graphing: Cognitive ability or practice?

Abstract: Traditional views conceive graphing as knowledge represented in students' minds. We show in our critique that such views lead to a common assessment problem of how to account for variations in performance across contexts and tasks, and a common attribution problem that locates difficulties in students' deficient cognitive apparatus. Grounded in recent research of scientists at work and everyday cognition, this article provides an alternative perspective that conceives of graphing as observable practices employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
12

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 39 publications
2
38
0
12
Order By: Relevance
“…Mevarech and Kramarsky (1997) reported that they developed a graphing course that, although it did reduce middle-school students' superficial graphing errors, it did not affect their more fundamental alternative conceptions about graphing. To overcome these problems, Roth and McGinn (1997) propose a social-cultural perspective focusing on students becoming graphing practitioners. This resonates with diSessa et al's (1991) study of students' meta-representational competency (diSessa and Sherin 2000) in which students did invent all sorts of idiosyncratic representations of motion.…”
Section: Graphingmentioning
confidence: 99%
“…Mevarech and Kramarsky (1997) reported that they developed a graphing course that, although it did reduce middle-school students' superficial graphing errors, it did not affect their more fundamental alternative conceptions about graphing. To overcome these problems, Roth and McGinn (1997) propose a social-cultural perspective focusing on students becoming graphing practitioners. This resonates with diSessa et al's (1991) study of students' meta-representational competency (diSessa and Sherin 2000) in which students did invent all sorts of idiosyncratic representations of motion.…”
Section: Graphingmentioning
confidence: 99%
“…The differences between these two are most evident by the ways graph interpretation is studied. Whereas the psychological research attempts to examine component skills, knowledge, and dispositions to interpret graphs using multiple choice tests and inferences made using test scores (Leinhardt, Zaslavsky, & Stein, 1990), the sociocultural research views learning to interpret graphs holistically, especially in science, often highlighting the interconnected nature of graphing (Roth & McGinn, 1997).…”
Section: Psychological and Sociocultural Literaturesmentioning
confidence: 99%
“…그래프는 실제의 다른 측면을 표현하는 기호학적 (semiotic) 대상이고, 과학적 의사소통에서 수사학적 (rhetorical) 기능을 하며, 공동 과학 활동을 중재하는 공유(conscription) 장치로서의 역할을 한다 (Roth and McGinn, 1997). 또한 그래프는 이미 공유된 논리적 인 자료의 배열과 시각적으로 우세한 장점으로 인해 수학과 과학은 물론이고 지리학, 경제학, 통계학 등 여러 학문 분야에서 폭넓게 사용되고 있다 (박현진, 2000; 성태제, 2001; 정광복, 2005).…”
Section: 서 론unclassified